PROFILE OF CARDIAC PREGNANT WOMEN: HIGH-RISK - Claudia Felczak; Ana Paula Xavier Ravelli; Suellen Vienscoski Skupien; Maria Helena Ricken; Laryssa De Col Dalazoana Bayer; Eva Aparecida Almeida (Universidade Federal do Paraná, 2018)
Objective: To characterize cardiac pregnant women with high-risk pregnancies assisted in a secondary healthcare unit at the Third Regional Health Center of the state of Paraná, Brazil. Methods: Quantitative, documentary and retrospective study carried out from July to August 2016. The investigation used secondary data from health indicators originated at the Campos Gerais High-Risk Pregnancy Clinic. The database search was restricted to the period between October 2013 and June 2016. Sixty medical records of cardiac pregnant women were analyzed using two variables: cardiac diagnosis, and sociodemographic factors and obstetric antecedents. Results: The most common cardiac diagnosis was cardiac arrhythmia and the prevalent cardiovascular risk factor was systemic arterial hypertension. The profile of patients assisted in this unit was a woman from the Castro municipality, 26.4 years old on the average, married, with complete primary school and multigravida. Conclusion: The main cardiac diagnosis among the examined women was cardiac arrhythmia, which increases cesarean indexes and makes the work of nurses in prenatal care fundamental to minimize possible complications.